Penggunaan Booklet terhadap Pengetahuan Anemia pada Remaja Putri - Yulianingsih, Endah; Suherlin, Ika; Aswad, Yusrin; Ischak, Wenny Ino; Hulawa, Dinda (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2020)
Anemia is still a reproductive health problem, especially in women whose hemoglobin levels are less than 12 g%. Education is one of the factors that influence the incidence of anemia and also greatly affects the ability to think in adolescents. The purpose of this study was to analyze health education through knowledge booklets about anemia in adolescents in Gorontalo City. This type of research uses the Pre-Experimental method with One-Group Pre-Test-Post Test Design, with a sample of 132 young women using a simple random sampling technique. The study started from February 1 to March 1, 2020. The analysis in this study used the Wilcoxon test. The results showed that there was a significant effect of health education through booklets on knowledge of anemia in adolescents with a sig value of 0.000 <0.05. The conclusion is that there is an effect of health education through booklets on knowledge about anemia in adolescent girls.